What will remain of us for tomorrows archaeologists? - United Nations Educational, Scientific; Cultural Organization; Jan Zalasiewicz; Sarah Gabbott (The UNESCO Courier, 2025)
Man-made minerals, synthetic plastic, concrete blocks, and inked sheets of paper are among the remnants of our civilization that future archaeologists will uncover, according to Jan Zalasiewicz and Sarah Gabbott, professors of paleobiology and authors of a book on the subject.